2006
DOI: 10.1111/j.1442-2050.2006.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of nuclear survivin expression in esophageal squamous cell carcinoma

Abstract: RUNNING TITLE: Nuclear survivin expression in ESCC 1 2 ABSTRACT Purpose. Despite advances in the treatment of esophageal carcinoma, the prognosis for this disease remains poor. Therefore, it is important to obtain a better understanding of the molecular basis of esophageal carcinogenesis. The purpose of this study was to clarify the roles of survivin in esophageal squamous cell carcinoma (ESCC). Methods.One hundred twenty-two ESCC surgical specimens resected from 1989 to 1999 were examined. Survivin expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…Although a prognostic value of survivin expression in esophageal cancer has been reported by several studies (29)(30)(31)(32)(33)36,38), there exist some conf licting data (29,42,43). In this context, our analysis revealed no significant correlation between survivin expression and overall survival in ESCC or EAC patients.…”
Section: Adenocarcinomacontrasting
confidence: 46%
See 1 more Smart Citation
“…Although a prognostic value of survivin expression in esophageal cancer has been reported by several studies (29)(30)(31)(32)(33)36,38), there exist some conf licting data (29,42,43). In this context, our analysis revealed no significant correlation between survivin expression and overall survival in ESCC or EAC patients.…”
Section: Adenocarcinomacontrasting
confidence: 46%
“…In ESCC survivin expression could be correlated with clinicopathological parameters and was linked to poor survival in the majority of published studies (29)(30)(31)(32)(33)(34)(35)(36). In contrast, the prognostic impact of XIAP expression and its association to pathological variables in ESCC patients has not yet been adequately investigated.…”
Section: Adenocarcinomamentioning
confidence: 99%
“…Concerning the studies using immunohistochemical examinations, three of the four studies reported nuclear survivin expression as a prognostic predictor in ESCC [9,12,13]. However, Dabrowski stated that survivin expression could not Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have been published concerning the implication of the correlation between survivin expression and clinicopathological parameters in ESCC [7][8][9][10]12,13,16]. Of these, four studies examined mRNA expression using RT-PCR and others examined protein expression by immunohistochemical staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation